Edukasi Media Pembelajaran Berbasis Digital Sebagai Upaya Meningkatkan Inovasi Pembelajaran Bagi Guru-Guru MGMP EKONOMI SMA Kabupaten Lamongan Jawa Timur - Imam Bukhori; Elfia Nora; I Nyoman Suputra (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Through using digital-based learning media, teachers can manage student assignments through a collaborative platform. By using digital-based learning media, students can access learning materials from anywhere. Some of the interactive digital-based learning media that can be used by teachers to teach are Genially which is used to create Powert Points, Google Sites, Book Creator used to make E-books, Animation studio to make learning animation videos, Blogger to share or publish learning materials to students. The problems of this community service partner are the teachers of MGMP Economics High School Lamongan Regency, namely: 1) There are still many teachers who have not used digital-based learning media in the learning process, 2) Teaching methods are still monotonous, with learning media that are not yet innovative. The solutions offered to overcome partner problems are: 1) Providing education about digital-based learning media to MGMP Economics teachers of Lamongan Regency, East Java, 2) Practice and assistance in making digital-based learning media. From the results of community service activities, it is known that 1) there are still many teachers who have not used digital-based learning media in the learning process, this can be seen from the number of teachers who are new to the application that can be used as a learning medium, 2) many teachers still use conventional learning media, because there is still a lack of knowledge and education about digital-based learning media applications.